More than a playground dispute: il caso Trinity Lutheran Church v. Pauley e le nuove traiettorie interpretative dell’Establishment Clause (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Il problema della legittimità di forme di assistenza finanziaria alle organizzazioni confessionali nell’ordinamento statunitense - 2. L’evoluzione della giurisprudenza della Corte Suprema - 3. I margini di discrezionalità dei singoli Stati - 4. Il caso Trinity Lutheran Church v. Pauley - 5. Le posizioni sostenute dalle parti - 6. Il confronto con il caso Locke v. Davey - 7. Il retaggio dei “Blaine Amendments” - 8. Il trattamento spettante alle istituzioni di natura religiosa - 9. La Corte Roberts e la clausola di separazione: nuove traiettorie interpretative.More than a playground dispute: the Trinity Luthera Church v. Pauley case and the new trajectories of the interpretation of the Establishment ClauseABSTRACT: This paper analyzes the problem of the access of nonprofit religiously affiliated organizations to the public funding necessary for these institutions to develop their mission: in the USA, nonprofit religiously affiliated organizations are denied direct access to public funding but some forms of indirect access have been gradually admitted. The article examines new perspectives opened by recent Supreme Court rulings, which are going to offer a new, more equal role to nonprofit religiously affiliated organizations, preserving their spiritual identity.
Keywords: Diritto ecclesiastico comparato e straniero